AKSI PEMBERDAYAAN DAN EDUKASI SECANTING (SEMANGAT CEGAH STUNTING) DI WILAYAH KERJA PUSKESMAS 4 ULU PALEMBANG - Resy Asmalia; Putri Rizki Amalia Badri; anggina, Dientyah Nur Anggina; Oktarina, Rizki; Habiburrahman, M. Dzaky; Memo Naufal Othman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Stunting is a condition of growth failure in children due to malnutrition for a very long time. The prevalence of stunting in South Sumatra reached 28.98%. Interventions that need to be done to reduce the prevalence start from the first 8000 days of life starting (HPK) from toddlers to adolescents. The purpose of this activity was to increase knowledge and improve the health of mothers, toddlers and adolescents so as to reduce the prevalence of stunting. The targets of this activity were mothers who have stunted toddlers, stunted toddlers and adolescent girls in the working area of Puskesmas 4 Ulu Palembang. The methods used were anthropometric measurements on toddlers and adolescents, haemoglobin measurements on adolescents, SECANTING education using snakes and ladders game media and crossword puzzles. Evaluation of the activity was carried out by giving a pretest-posttest questionnaire. The service team involved were the lecturers of FK UMPalembang, UMPalembang’s cross-program students and the PERMAHUM Organisation of South Sumatera. The results of this activity were that participants understood the efforts of providing high protein supplementary food for toddlers and preventing anaemia in adolescent girls as a form of stunting prevention. Suggestions that can be given are to conduct stunting education routinely to reduce the prevalence of stunting and improve the health status of the Indonesian people. Abstrak Stunting adalah kondisi gagal tumbuh pada anak akibat kekurangan gizi dalam waktu yang sangat lama. Prevalensi stunting di Sumatera Selatan mencapai 28.98%. intervensi yang perlu dilakukan untuk menurukan prevalensi tersebut dimulai dari 8000 Hari Pertama Kehidupan dimulai dari balita hingga remaja. Tujuan dari kegiatan ini adalah untuk menambah pengetahuan serta meningkatkan kesehatan ibu, balita dan remaja sehingga dapat menurunkan prevalensi stunting. Sasaran pada kegiatan ini adalah ibu yang memiliki balita stunting, balita stunting dan remaja putri di wilayah kerja Puskesmas 4 Ulu Palembang. Metode yang dilakukan adalah pengukuran antropometri pada balita dan remaja, pengukuran hemoglobin pada remaja, edukasi SECANTING menggunakan media permainan ular tangga dan teka-teki silang. Evaluasi kegiatan dilakukan dengan pemeberian kuesioner pretest-posttest. Tim pengabdian yang dilibatkan adalah dosen FK UMPalembang, mahasiswa lintas prodi UMPalembang dan Organisasi PERMAHUM Sumatera Selatan. Hasil dari kegiatan ini adalah peserta memahami upaya pemberian makanan tambahan tinggi protein bagi balita dan pencegahan anemia pada remaja putri sebagai bentuk pencegahan stunting. Saran yang dapat diberikan adalah melakukan edukasi stunting secara rutin untuk menurunkan prevalensi stunting dan meningkatkan derajat kesehatan masyarakat Indonesia